2009
DOI: 10.1124/dmd.109.029637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cynomolgus Monkey Pregnane X Receptor, Primary Hepatocyte, and in Vivo Pharmacokinetic Changes in Predicting Human CYP3A4 Induction

Abstract: ABSTRACT:Monkeys have been proposed as an animal model to predict the magnitude of human clinical drug-drug interactions caused by CYP3A4 enzyme induction. To evaluate whether the cynomolgus monkey can be an effective in vivo model, human CYP3A4 inducers were evaluated both in vitro and in vivo. First, a full-length pregnane X receptor (PXR) was cloned from the cynomolgus monkey, and the sequence was compared with those of rhesus monkey and human PXR. Cynomolgus and rhesus monkey PXR differed by only one amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 25 publications
(25 reference statements)
3
28
0
Order By: Relevance
“…The EC 50 values for the two hepatocyte preparations were 2.4 M (95% confidence interval, 1.1-5.2 M) and 1.7 M (95% confidence interval, 1.0 -3.0 M). These results were comparable with the previously reported EC 50 values (0.67-2.34 M) for the induction of MDZ 1Ј-hydroxylase activity by RIF in cynomolgus monkey hepatocytes (Kim et al, 2010).…”
Section: Apz Metabolism In Liver and Smallsupporting
confidence: 82%
See 1 more Smart Citation
“…The EC 50 values for the two hepatocyte preparations were 2.4 M (95% confidence interval, 1.1-5.2 M) and 1.7 M (95% confidence interval, 1.0 -3.0 M). These results were comparable with the previously reported EC 50 values (0.67-2.34 M) for the induction of MDZ 1Ј-hydroxylase activity by RIF in cynomolgus monkey hepatocytes (Kim et al, 2010).…”
Section: Apz Metabolism In Liver and Smallsupporting
confidence: 82%
“…However, concentration-response relationships could vary among inducers, nuclear receptors, or the species examined. Kim et al (2010) investigated PXR transactivation profiles of 30 compounds, including known CYP3A4 inducers, in reporter assays, demonstrating that EC 50 values correlated well between cynomolgus and human PXRs, although there were notable species differences in EC 50 and E max values for reserpine. Thus, further studies using other inducers are required for a better understanding of similarities and differences in CYP3A induction in vivo between humans and monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…7) It was previously reported that cmCYP3A4 (3A8) is induced by RIF through the transcription factor PXR. 29) Our study showed that PXR is expressed in cmESC-derived hepatic cells. These results suggest that PXR is active in these hepatocytes.…”
Section: Discussionmentioning
confidence: 96%
“…Macaque CYP3A8(4) metabolizes typical human CYP3A4 substrates such as midazolam and nifedipine (Iwasaki et al, 2010;Uno et al, 2010) and is induced by the typical human CYP3A4 inducer, rifampicin (Kim et al, 2010), indicating that CYP3A8(4) has drug-metabolizing enzyme properties similar to human CYP3A4. Induction of cynomolgus macaque CYP3A8(4) and human CYP3A4 by rifampicin is mediated via PXR (Kim et al, 2010), which binds to the regulatory element in the upstream region of CYP3A4, suggesting that the regulatory region of cynomolgus macaque CYP3A8(4) and human CYP3A4 is conserved well between macaque and human. Induction of CYP3A8(4) expression in macaque liver by estradiol, therefore, raises the possibility that CYP3A4 is also regulated by estradiol in human liver.…”
Section: Estradiol-regulated Drug-metabolizing Enzymes In Macaquementioning
confidence: 99%